2019
DOI: 10.1074/jbc.aac119.011308
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Phosphoglycolate phosphatase is a metabolic proofreading enzyme essential for cellular function in Plasmodium berghei.

Abstract: During copy editing, an error was introduced in a column label in Table 1. The label of the last column should be k cat /K m. This error has now been corrected and does not affect the results and conclusions of this work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Loss of phosphoglycolate phosphatase in yeast and other human cells perturbs metabolism [126], but the cells are viable. In contrast, the enzyme is essential in Plasmodium berghei [129].…”
Section: Metabolite Repairmentioning
confidence: 96%
See 2 more Smart Citations
“…Loss of phosphoglycolate phosphatase in yeast and other human cells perturbs metabolism [126], but the cells are viable. In contrast, the enzyme is essential in Plasmodium berghei [129].…”
Section: Metabolite Repairmentioning
confidence: 96%
“…Hydrolysis of 1,4-bisphosphoerythronate by an unknown mechanism (possibly a promiscuous enzyme) produces 4-phosphoerythronate, a potent inhibitor of 6-phosphogluconate dehydrogenase in humans, yeast [126,128] and Bacillus subtilis [128]. Inhibition of 6-phosphogluconate dehydrogenase leads to elevated levels of its substrate, 6-phosphogluconate, which in turn inhibits phosphoglucose isomerase, decreasing flux through glycolysis and impairing or even abolishing growth [128,129]. Phosphoglycolate phosphatase (a polyspecific enzyme named for its ability to hydrolyze a by-product of oxidative damage to DNA) hydrolyzes 4-phosphoerythronate in human and yeast cells with a very respectable k cat /K M of >10 4 M −1 s −1 .…”
Section: Metabolite Repairmentioning
confidence: 99%
See 1 more Smart Citation
“…Toxic metabolic side products are generated in cells due to mutations in enzymes, changes in metabolic flux or due to the enzyme reaction with alternative substrates at low rates as the specificity of many enzymes is not absolute. Thus, it was shown that GAPDH can also catalyze the conversion of the pentose phosphate pathway metabolite erythrose-4-phosphate to 4phosphoerythronate ( 51), though at a much lower rate (32) (33,53), it was suggested that G3PP/PGP can act like a 'metabolic repair enzyme' and hydrolyze these two toxic metabolites. However, as the concentrations of these metabolites in wild type cells with normal expression of G3PP/PGP are much lower than their corresponding Km for purified mouse G3PP/ PGP, it is plausible that only under stress conditions when these metabolites accumulate significantly, G3PP/PGP may hydrolyze them and act as a detoxification enzyme of various phosphometabolites, besides its action on Gro3P.…”
Section: Detoxification Of Metabolic By-products Of Enzymatic Reactionsmentioning
confidence: 99%
“…4-Phosphoerythronate and 2-phospholactate were shown to inhibit 6-phosphogluconate dehydrogenase and phosphofructokinase-2, respectively ( 32 ). As 4-phosphoerythronate and 2-phospholactate accumulate only in PGP deleted HCT116 cells ( 32 ) and malarial parasite Plasmodium ( 33 , 53 ), it was suggested that G3PP/PGP can act like a ‘metabolic repair enzyme’ and hydrolyze these two toxic metabolites. However, as the concentrations of these metabolites in wild type cells with normal expression of G3PP/PGP are much lower than their corresponding Km for purified mouse G3PP/PGP, it is plausible that only under stress conditions when these metabolites accumulate significantly, G3PP/PGP may hydrolyze them and act as a detoxification enzyme of various phospho-metabolites, besides its action on Gro3P.…”
Section: Physiological Roles Of G3pp/pgpmentioning
confidence: 99%